2008
DOI: 10.1136/jnnp.2006.111518
|View full text |Cite
|
Sign up to set email alerts
|

Neurological evaluation of patients with Gaucher disease diagnosed as type 1

Abstract: Type 1 Gaucher disease (GD1) is characterised by lack of central nervous system involvement; however, there are several reports of associated neurological manifestations. The aim of this study was to systematically evaluate neurological manifestations in 31 patients with GD1 (12 males and 19 females; mean age 39.4 (range 5-77) years). Participants underwent a complete neurological examination and cognitive tests. Investigation of symptoms and medication intake, and motor and sensory electroneurograms were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 13 publications
2
43
0
2
Order By: Relevance
“…Neurological manifestations of GD3 in juvenile patients are characterized by dysfunction of the major motor circuits, myoclonic epilepsy, oculomotor abnormalities and intellectual deterioration. The neurological abnormalities observed in our adult patients with GD1, and in recently published surveys, are predominantly parkinsonian symptoms and peripheral neuropathies (Halperin et al 2007;Hollak et al 2007;Capablo et al 2008;Cherin et al 2006). Thus, differences in the types of neurological dysfunction seen clinically, according to GD phenotype, suggest distinct neuropathologies within each GD phenotype.…”
Section: Pathophysiology Of the Main Neurological Manifestations In Gd1supporting
confidence: 58%
See 2 more Smart Citations
“…Neurological manifestations of GD3 in juvenile patients are characterized by dysfunction of the major motor circuits, myoclonic epilepsy, oculomotor abnormalities and intellectual deterioration. The neurological abnormalities observed in our adult patients with GD1, and in recently published surveys, are predominantly parkinsonian symptoms and peripheral neuropathies (Halperin et al 2007;Hollak et al 2007;Capablo et al 2008;Cherin et al 2006). Thus, differences in the types of neurological dysfunction seen clinically, according to GD phenotype, suggest distinct neuropathologies within each GD phenotype.…”
Section: Pathophysiology Of the Main Neurological Manifestations In Gd1supporting
confidence: 58%
“…A recent systematic investigation assessed neurological manifestations in 28 GD1 patients, 30.7% of whom had neurological deficits (Capablo et al 2008). The most frequent finding amongst these affected patients was subclinical peripheral neuropathy, as identified by electrophysiological examination in 40% of those who underwent this examination (n=15).…”
Section: Gd1 and Peripheral Neuropathymentioning
confidence: 99%
See 1 more Smart Citation
“…As we mentioned before the N370S mutation has been traditionally associated with the absence of neurological disease; however, several studies reported a high proportion of patients with the N370S mutation were diagnosed with GD 1 and showed mild neurological symptoms such tremor, peripheral neuropathy, uncoordinated movements, and hearing loss (as well as Parkinson disease. (Capablo et al, 2008;Giraldo et al, 2011;Pastores et al, 2003). These findings are consistent with the recently established contention that the mutation could not fully protect the patient from the appearance of neurological symptoms (Halperin et al, 2007).…”
Section: Mutations In Gba and Neuronopatic Forms Of Gaucher Diseasesupporting
confidence: 90%
“…Although type 1 GD occurs in the general population, Ashkenazi Jews are more likely to contract type 1 GD (Hruska et al , 2008 ). While type 1 GD is considered non-neuropathic, a subset of patients show neurological symptoms such as parkinsonism, dementia, and subclinical peripheral neuropathy (Neudorfer et al , 1996 ;Biegstraaten et al , 2008 ;Capablo et al , 2008 ;Alonso -Canovas et al, 2010 ). Many studies have suggested a link between type 1 GD and Parkinson ' s disease (PD).…”
Section: Introductionmentioning
confidence: 99%